The Effect of Soaking in Lemon Water and Packaged Lemon Water on Changes in Surface Roughness of Nanofiller Composite Resin. - Irsan Ibrahim; Tuti Alawiyah; Narulita N (Journal of Indonesian Dental Association, 2026)
Introduction: Composite resin is currently one of the most commonly used restorative materials in dentistry due to its excellent esthetic properties and its ability to closely resemble the natural color of teeth. Exposure to acidic beverages, such as fresh lemon juice and commercially packaged lemon drinks (You-C 1000), may influence the surface characteristics of composite resin restorations, particularly surface roughness, depending on the duration of immersion. Objective: This study aimed to evaluate the effect of immersion in fresh lemon juice and packaged lemon beverage on the surface roughness of nanofiller composite resin. Methods: This study was an in vitro laboratory experimental study using a pre-test and post-test control group design. Nanofiller composite resin specimens were immersed in lemon juice solution (pH = 3.14) and packaged lemon beverage solution (pH = 3.67) for 3 hours. Surface roughness measurements were performed before and after immersion. Results: Surface roughness increased from 0.061 ± SD µm to 0.086 ± SD µm in the lemon juice group, from 0.065 ± SD µm to 0.072 ± SD µm in the packaged lemon beverage group, and from 0.055 ± SD µm to 0.059 µm in the distilled water group. The differences among groups were statistically significant (p < 0.05).. Conclusion: Immersion in fresh lemon juice and packaged lemon beverage significantly affected the surface roughness of nanofiller composite resin.